Pyridazine and its related compounds: Part 32. Synthesis and antimicrobial evaluation of some 3-substituted amino-4,5,6-triphenylpyridazine derivatives - Deeb, Ali Abdel Hamid; El-Mariah, Fatma Abdel Rahman; El-Mawgoud, Heba Kamal Abd (European Journal of Chemistry, 2015)
3-Amino-4,5,6-triphenylpyridazine was subjected to some selected reactions with nitrous acid, formic acid/dimethylformamide, acetic anhydride, benzoyl chloride, chloroacetyl chloride, acetaldehyde, diethyl malonate, malonic acid/phosphoryl chloride, diethyl oxalate, ethyl cyanoacetate, ethyl acetoacetate, and ethyl benzoylacetate to give new 3-substituted aminopyridazine derivatives. A few sulfonamide derivatives (new) were also prepared. The structures of the synthesized compounds were proved by their infrared, mass spectra, 1H NMR, and elemental analysis. The antimicrobial activity of the compounds obtained was examined against some selected microorganisms.